Application of Chromatography Methods for the Separation and Detection of Certain Benzodiazepine Drugs in Forensic Sample - Gurusamy, Karuppasamy; Cyril, A.; Thangadurai, Subbiah (Pharmaceutical Research: Recent Advances and Trends Vol. 7, 2024)
Benzodiazepines (BZDs) are widely used in pharmacotherapy as antiepileptic, muscle relaxant, hypnotic, and anesthetic inductors. These drugs were once an occasional problem, today they have become much more common. Due to the structural similarity of the specimens encountered by the forensic laboratory, an array of instruments is needed to correctly identify these substances. Any of the BZDs can be identified by combining the results obtained with different mobile phases. For pharmaceutical sample preparation, each type of BZD tablet was accurately weighed and powdered in a mortar. Ten milligrams were taken and dissolved in 10 mL of methanol and sonicated for five minutes. Forensic Scientists are required to identify an ever-increasing and more complex assortment of drugs and related compounds. Rapid, sensitive, and specific thin-layer chromatography (TLC), high-performance liquid chromatography (HPLC), and gas chromatography-mass spectrometry (GC-MS) methods were utilized for the analysis of certain benzodiazepines (BZDs). HPLC proposes a cost-efficient method with the ruggedness and consistency necessary for forensic testing and consequently is widely used in forensic laboratories today. GC-MS is one of the most commonly used techniques for the identification and quantitation of forensic drug samples. As a “hyphenated” technique, it combines the separation power of a GC with the analyte specificity of a spectroscopic technique, provided that vastly specific spectral data on individual compounds in a complex mixture often devoid of prior separation. We succeeded in the separation of the encountered BZD drug diazepam in the forensic sample. The method was validated for linearity, accuracy, precision, and limit of detection. This method could be potentially applied in the analysis of forensic samples from drug-facilitated sexual assault cases. A competent forensic toxicologist relies on their own case experience as well as the unique state of affairs of each case under assessment.